Effects of the Enhanced Recovery After Surgery Protocol on Postoperative Recovery, Sleep Quality, and Postpartum Depression in Elective Cesarean Section Patients: A Single-Center, Prospective Study - Keleş Tayfur, Elif; Keskin, Deha Denizhan (The European Research Journal, 2026)
Objective: To assess the effects of the Enhanced Recovery After Surgery–Cesarean Delivery (ERAS-CD) protocol on early postoperative recovery, pain scores, postpartum sleep quality, and postpartum depression in patients undergoing elective cesarean delivery. Methods: This single-center prospective cohort study involved women with at least one cesarean delivery who underwent planned CD between December 2022 and May 2023. The primary outcome was to reduce hospital stay and morbidity following CD. Secondary outcomes included breastfeeding/formula supplementation status, postoperative pain score, postpartum sleep quality, and predisposition to postpartum depression. The protocol included preoperative oral intake of cherry juice, multimodal analgesia, antiemetic medications, and early ambulation. The number of patients and minimum sample size per group were determined based on power analysis results from previous studies. Results: A total of 294 patients were included in the study. The ERAS-CD protocol group and the control group were similar in demographic characteristics, body weight, and parity (P>0.05). Postoperative Visual Analog Scale and severe pain scores were lower in all components of the ERAS-CD protocol group (P